Near-Field Scattering Phenomena in Monostatic Radar Applications Derived From Physical Optics - Tegowski, Bartosz; Langer, Dominik; Wenzel, Marvin; Albrecht, Nils C.; Kölpin, Alexander (IEEE Transactions on Antennas and Propagation, 2024)
In the context of radar, this article examines phenomena that occur in conditions where the physical extent of the target cannot be considered negligible compared to the range and, thus, far-field assumptions are violated. Based on physical optics principles, a transfer function of the radar channel between the antenna input and output power wave is derived for a monostatic configuration. The effects are studied using a circular metallic disk as an exemplary target. Exact and approximative expressions for the transfer function are derived incorporating the influence of the antenna radiation characteristic in addition. Measurements with targets of different sizes performed with horn as well as open-ended waveguide antennas at 24 and 61 GHz validate the phenomena of receive power level fading and nonlinear phase distortio
Keywords: Accuracy; channel modeling; near-field effects; physical optics; radar cross section (RCS); radar theory; wave propagation; Radar antennas; Radar; Radar cross-sections; Antennas; Transfer functions; Receiving antennas; Antenna measurements; Surface waves; Physical optics; Optical surface waves